2012
DOI: 10.1371/journal.pone.0042305
|View full text |Cite
|
Sign up to set email alerts
|

Tungstate Reduces the Expression of Gluconeogenic Enzymes in STZ Rats

Abstract: AimsOral administration of sodium tungstate has shown hyperglycemia-reducing activity in several animal models of diabetes. We present new insights into the mechanism of action of tungstate.MethodsWe studied protein expression and phosphorylation in the liver of STZ rats, a type I diabetes model, treated with sodium tungstate in the drinking water (2 mg/ml) and in primary cultured-hepatocytes, through Western blot and Real Time PCR analysis.ResultsTungstate treatment reduces the expression of gluconeogenic enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 42 publications
(57 reference statements)
1
37
0
Order By: Relevance
“…Prior studies have pointed to different target tissues for tungstate actions depending on the model investigated. Thus, tungstate has been shown to normalize hepatic glucose metabolism in streptozotocin (STZ) and Zucker diabetic rats (5,20,37) to improve ␤-cell function in neonatal and adult STZtreated rats (1,3,21) or to modulate energy homeostasis in obese rats (2,7,18). Remarkably, the normoglycemic effects of tungstate in STZ-treated rats were associated with an increase in ␤-cell mass (3,21).…”
mentioning
confidence: 99%
“…Prior studies have pointed to different target tissues for tungstate actions depending on the model investigated. Thus, tungstate has been shown to normalize hepatic glucose metabolism in streptozotocin (STZ) and Zucker diabetic rats (5,20,37) to improve ␤-cell function in neonatal and adult STZtreated rats (1,3,21) or to modulate energy homeostasis in obese rats (2,7,18). Remarkably, the normoglycemic effects of tungstate in STZ-treated rats were associated with an increase in ␤-cell mass (3,21).…”
mentioning
confidence: 99%
“…Hepatic gluconeogenesis has an important influence on glucose metabolism [37]. Additionally, insulin deficiency is closely correlated with hepatic glucose output via increased expression of PEPCK that is a key enzyme of hepatic carbohydrate metabolism in diabetic hyperglycemia [28, 38, 39]. Liver-specific inhibition of PEPCK with RNAi improved diabetic hyperglycemia [40].…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of Na 2 WO 4 used to evaluate the antidiabetic effect was around 6 mM [18,19]. Toxicity was not reported in animal studies [17,18,45] or in vitro [20] as an antidiabetic agent. Moreover, Na 2 WO 4 was studied in obese nondiabetic patients without any toxicity effect [46].…”
Section: Figmentioning
confidence: 99%
“…Therefore, insulin mimetics have been sought. Sodium tungstate (Na 2 WO 4 ) is a water soluble inorganic compound that can exert an insulin-like effect in diabetes [16,17]. Several studies have shown that oral administration of Na 2 WO 4 into animal models of type 1 and type 2 diabetes normalizes glycemia without hypoglycemia [17][18][19].…”
Section: Introductionmentioning
confidence: 99%